Vegetative and reproductive phenology of Copaifera langsdorffii Desf. in different phytophysiognomies (Research, Society and Development, 2022)
The phenology has been discussed according to climatic variations and the environmental characteristics of each physiognomy, trying to identify if there is variation in the vegetative and reproductive phenophases, for Copaifera langsdorffii Desf. in areas of the Cerradão, Carrasco and Humid Forest, Chapada do Araripe in Northeast Brazil and if they are correlated with seasonality. Monthly observation censuses were conducted on 10 individuals from each area from January 2019 to December 2020. The continuous, sub-annual, annual, and supra-annual classes were taken into account. The intensity and synchrony of individuals were evaluated, and seasonality was tested using Spearman's correlation with local weather variables. The species presented a semi-deciduous vegetative phenological strategy, with peaks occurring mainly at the end of the rainy season and the beginning of the dry season. The flowering pattern of C. langsdorffii was considered annual and seasonal, because flowering occurred at similar periods in the three areas, with peaks in December and January. Fructification occurred annually, with seasonality only in the phyto-physiognomy of the Cerradão. C. langsdorffii bore fruit during the rainy season in the Cerradão, Carrasco and Humid Forest, with the exception only of 2020 in the Carrasco and Humid Forest, where individuals bore fruit during both the rainy and dry seasons. According to the correlation results, precipitation, temperature, and humidity shape the reproductive patterns of C. langsdorffii, which may also occur in populations of this species in other environments.